Enhancing the Viability of Rosella Seeds (Hibiscus sabdariffa L.) through Tetrazolium and Paper Media Test - Taufiq Hidayat RS; Mayasari Yamin (Universitas Sembilanbelas November Kolaka, 2019)
This study was aimed to determine the viability rate of rosella seed, to obtain the best result of seed testing for enhancing rosella seed viability, to find the best seed invigoration method for enhancing rosella seed viability, to obtain staining pattern through tetrazolium test of rosella seed, and to determine viability and vigor of rosella seed to be further used as estimation indicator for rosella plant growth in the field. The study was conducted in the Seed Laboratory, Indonesian Sweetener and Fiber Crops Research Institute (ISFCRI), Malang, East Java during July - August 2018. The material used included accessions of rosella seed (Hibiscus sabdariffa L.) ACC. 1148 from the year 2015 and collection of ISFCRI, 100 ml of Tetrazolium solution (40 ml KH2PO4, 60 ml Na2HPO4 and 1 gr of Tetrazolium powder). This research applied Completely Randomized Design (CRD) consisted of seed treatments of control (no immersion/0 hour), immersion for 5 hours, immersion for 10 hours, and scarification, each with 4 replications. Result of this study showed that the use of tetrazolium salt was found to be better in enhancing the viability of rosella seeds. Viable seeds was found to have bright red embryonic axis and bright red cotyledon. Testing using paper media on several seed invigoration treatments resulted in significantly different effect on parameters of vigor index, germination capacity, and dry weight of normal seedling. The best parameter of germination capacity and dry weight of normal seedling was obtained by treatment immersed in water at temperature of 27°C for 10 hours